Pengembangan Media Pembelajaran Interaktif Gather Town pada Materi Rapat di SMKN 1 Surabaya - Ratna Safitri; Durinta Puspasari (Universitas Negeri Surabaya, 2022)
This study aims to analyze the development of gather town interactive learning media in meeting materials at SMK Negeri 1 Surabaya and is used to determine how the feasibility of developing and evaluating students towards the development of gather town media as an alternative learning medium in the subject of automation of public relations and protocol governance at SMK Negeri 1 Surabaya. This type of research uses Research and Development (R&D) research using the ADDIE development model developed by Raiser and Mollenda. The development of this media gather town went through 5 stages, namely: 1) Analysis, 2) Design, 3) Development, 4) Implementation. 5) Evaluation, but only carried out until the fourth stage, namely Implementation because the purpose of this research is limited to developing and producing valid learning media to be applied based on the validator's assessment of pre-existing media. Based on the results of this study indicate that the quality of media feasibility can be seen through the results of the validation of experts and student evaluations. The percentage obtained from material validators conducted by Lecturers of Office Administration Education and Teachers of Public Relations and Protocol Management Automation at SMK Negeri 1 Surabaya is 92.1% with a Very Eligible category, which means that the material for automation of public relations management and protocols on the basic competencies of implementing proper meetings used in this medium. The percentage obtained from the media validator carried out by Multimedia Teachers at SMK Negeri 1 Surabaya is 81.1% with the Very Eligible category, which means that gather town learning media is eligible to be used. The results of the percentage of student responses in class XII OTKP 4 SMK Negeri 1 Surabaya are 94.4% in the Very Eligible category, which means that gather town learning media is eligible to be used as a learning medium.